The climate-care nexus: Input to the study on care and support, pursuant to HRC resolution 54/6 - Anna Eknor Ackzell; Francisco Cos-Montiel; María Estrada; Fabio Vélez (United Nations Research Institute for Social Development (UNRISD), 2025)
There is a growing scientific consensus that climate change induced crisis and environmental degradation impact males and females differently and exacerbate pre-existing gender inequalities in the world of work. One main area of this gendered impact is paid and unpaid care work, which is provided for by women and girls to a greater extent than men and boys. The care burden increases during climate change induced crisis such as heat waves, natural catastrophes and overall environmental degradation, including drought, increased periods of flooding and desertification. Climate change induced crisis also taxes the health care system, which is largely a feminized labour sector. When we recognize that the "care crisis" is aggravated by the climate crisis and environmental degradation, it is clear that the intersection of the two has a more severe impact for groups of people that are also affected by other categories of difference in their individual lives, social practices, institutional arrangements and localities. In this way, the impact of climate change as well as the care crisis needs to be understood from an intersectional perspective in order to avoid exacerbating the often-concealed interests of less powerful parties, benefitting hegemonic interests. If until a few years ago the climate and care agendas did not seem to find points of contact, they are now beginning to be thought of as inseparable. Indeed, if the care crisis warned of the necessary interdependence of people and generations for the sustainability of societies, and the climate and environmental crisis warned of the inexorable eco-dependence that links us with our planet and with all forms of life, we now know that the care of life in general is a necessary condition for its sustainability. This note is a call for action for policymakers and the research community to engage with the topic of the climate-care nexus and examine its impact on the human rights of unpaid and paid caregivers, recipients of care and self-care of caregivers and recipients of care, including those who are women and girls, persons with disabilities, children and older people.
Keywords: 330; Klimawandel; Pflegeberufe; Häusliche Pflege; Geschlechterdiskriminierung